Sistem Pakar Mendiagnosa Penyakit Akibat Penggunaan Vape Menggunakan Metode Adaptive Neuro Inference System - Sari, Raska Rezki Permata (ADA Research Center, 2025)
Vape is an electric cigarette that is widely used as a temporary escape for those who have a little difficulty in trying to quit smoking. Vape produces steam into the air which contains fine nicotine and other harmful substances, the nicotine contained in the vape will be absorbed by the body. The vapors that emerge from vape cigarettes are not water vapor, but they contain nicotine and other harmful substances that are clearly not good for health and can also pollute the air. Several studies have shown that chemicals in e-cigarettes can damage lung tissue and reduce the ability of lung cells to protect the lungs from germs and other harmful substances. ANFIS method is an adaptive system based on fuzzy logic inference that combines two methods, namely adaptive (neural metwork) and fuzzy methods. This adaptive network is used to adapt the fuzzy logic inference system to represent the desired fuzzy interference system. The principle of the working method is to combine two methods, namely the adaptive method and the fuzzy method where both use the same two sources of information, but the representation is different. The results of diagnosing vape-related diseases are lung infection, hypotension, and heart failure, but the disease that is often caused by vape is lung infection, with an expert system diagnosing vape-related diseases that make it easier to find out the effects of vape use.